Workforce and supply chain disruption as a digital and technological innovation opportunity for resilient manufacturing systems in the COVID-19 pandemic. (July 2022) - Ambrogio, Giuseppina; Filice, Luigino; Longo, Francesco; Padovano, Antonio
Highlights: COVID-19 impacts on the workforce and supply as an innovation opportunity. Exploiting the potential of Human Cyber-Physical Production System in a pandemic. Defining the Plug-and-play worker, Remote Operator 4.0 and Predictive Health of Operational Staff. Fostering digital sourcing (i.e. additive manufacturing) and product/process innovation. Lessons learned from prototype development and real world business examples are discussed. Abstract: During the SARS-CoV-2 pandemic (also known as COVID-19), workforce downsizing needs, safety requirements, supply chain breaks and inventory shortages affected manufacturing systems' and supply chain's responsiveness and resilience. Companies wandered in a disrupted scenario because recommended actions/strategies to survive – and thrive – were not available an improvised actions to keep their operations up and running. This paper analyzes the COVID-19 impacts on the workforce and supply resilience in a holistic manner. The following research questions are discussed: (i) how can manufacturing firms cope with urgent staff deficiencies while sustaining at the same time a healthy and safe workforce in the perspective of socially sustainable and human-centric cyber-physical production systems?; (ii) is remote working (cf. smart working) applicable to shop-floor workers?; (iii) is it possible to overcome supply chain breaks without stopping production? In the first part, we propose three Industry 4.0-driven solutions that would increase the workforce resilience, namely: (i) the Plug-and-Play worker ; (ii) the Remote Operator 4.0 ; (iii) the Predictive Health of the Operational Staff . In the second part, the concepts of (i) Digital & Unconventional Sourcing, i.e. Additive Manufacturing, and (ii) Product/Process Innovation are investigated from a novel business continuity and integration perspective. We ultimately argue that forward-looking manufacturing companies should turn a disruptive event like a pandemic in an opportunity for digital and technological innovation of the workplace inspired by the principles of harmonic digital innovation (that places the human well-being at the center). These aspects are discussed with use cases, system prototypes and results from research projects carried out by the authors and real-world examples arising lessons learned and insights useful for scientists, researchers and managers.